Immunoadjuvanted influenza vaccine immunogenicity in children with type 1 diabetes over two consecutive seasons - Kostinov, Mikhail Petrovich; Kvasova, Maria Alexandrovna; Tarasova, Alla Anatolievna; Vlasenko, Anna; Kolbasina, Elena Vladimirovna; Bydanova, Darya Alexandrovna; Kostinova, Aristitsa; Polishchuk, Valentina; Khrapunova, Isabella Abramovna; Loktionova, Marina; Linok, Andrey Viktorovich; Dagil, Yulia Alekseevna; et al. (Frontiers in Immunology, 2025)
Patients with diabetes mellitus face a significantly higher risk of severe influenza and its complications. The purpose of this study was to investigate the immunogenicity of the trivalent immunoadjuvanted subunit influenza vaccine in children with type 1 diabetes (T1D) over two consecutive seasons.MethodsA prospective non-randomized study during 2 epidemic seasons included 146 children with T1D at the age of 12.0 (9.0-14.0) years; the main group consisted of 81 patients vaccinated against influenza, the control group included 65 unvaccinated children. Antibody (Ab) levels to influenza viruses were evaluated using the hemagglutination inhibition assay before vaccination, one month and 12 months after vaccination.ResultsOver two seasons, vaccinated children with T1D demonstrated a significant increase in Ab against all three vaccine strains 1 month post-vaccination, irrespective of their initial specific Ab levels. Differences in the persistence of antibodies 12 months post-vaccination were observed between children initially seronegative for A/H1N1 and A/H3N2 strains, who exhibited lower antibodies levels and fold increases, and those initially seropositive. Vaccinated seropositive children experienced significant post-vaccination Ab increases, surpassing levels in initially seronegative patients. Regardless of the epidemiological season, vaccination significantly increased the chance of achieving a seroprotective Ab level within one month for the A/H1N1 strain by 4.7 [2.9-9.7] (χ²M-H = 16.4, p < 0.001), for the A/H3N2 strain by 15.8 [5.9-41.4] (χ²M-H = 44.0, p < 0.001), and for strain B by 14.8 [6.5-33.6] (χ²M-H = 46.2, p < 0.001). Twelve months post-vaccination, Ab persistence was highest for the B strain, with levels 7.2 [3.2–16] times higher than in unvaccinated children, regardless of the season. Persistence of antibodies to the A/H1N1 strain was season-dependent (lower in the 2015-2016 season) and 2.5 [1.3-5] times higher than in unvaccinated children (χ²M-H = 6.5, p = 0.01). Antibodies persistence to the A/H3N2 strain did not differ significantly between vaccinated and unvaccinated groups (1.0 [0.5-2.3], χ²M-H = 0.02, p = 0.89).ConclusionAdministration of the trivalent immunoadjuvanted subunit influenza vaccine in children with T1D resulted in the formation of postvaccination Ab, meeting the Committee for Proprietary Medicinal Products (CPMP) immunogenicity criteria regardless of vaccination history.